Visual marking: Using time in visual selection - Watson, D; Humphreys, G; Olivers, C (2003)
Given human capacity limitations, to behave adaptively we need to prioritise the order of visual processing to ensure that the most relevant information is available to control action. One way to do this is to prioritise processing at a particular location in space. However, there are many situations where this strategy is not possible and recent studies have shown that, in such circumstances, observers can use time as well as space to prioritise selection. We propose that selection by time can be influenced by a process of visual marking, involving an active bias applied in parallel against old items in the field. Here we describe the properties of visual marking in relation to other mechanisms of visual selection.